2016
DOI: 10.5713/ajas.16.0041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coated Compound Proteases on Apparent Total Tract Digestibility of Nutrients and Apparent Ileal Digestibility of Amino Acids for Pigs

Abstract: Two experiments were conducted to evaluate effects of coated compound proteases (CC protease) on apparent total tract digestibility (ATTD) of nitrogen (N) and energy, and apparent ileal digestibility (AID) of amino acids (AA) and nutrients in diets for pigs. In Exp. 1, 12 crossbred barrows (initial body weight: 20.14±1.71 kg) were housed in individual metabolism crates and allotted into 2 treatments with 6 piglets per treatment according to weight in a randomized complete block design. The 2 diets were corn-so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…2). The improved nutrient digestibility in this study was similar to results reported by previous studies [11,27,28]. Addition of exogenous enzymes in non-ruminant diets has been using for several benefits including, minimization of anti-nutritional effects and maximization of nutrient utilization, to improve nutrient utilization and growth performance of non-ruminants [29] because the digestive system and the secretion and activity of digestive enzymes of young non-ruminants are immature and insufficient Sangwoo Park, et al Each value is the mean of 5 replicates (5 pigs/pen).…”
Section: Resultssupporting
confidence: 92%
“…2). The improved nutrient digestibility in this study was similar to results reported by previous studies [11,27,28]. Addition of exogenous enzymes in non-ruminant diets has been using for several benefits including, minimization of anti-nutritional effects and maximization of nutrient utilization, to improve nutrient utilization and growth performance of non-ruminants [29] because the digestive system and the secretion and activity of digestive enzymes of young non-ruminants are immature and insufficient Sangwoo Park, et al Each value is the mean of 5 replicates (5 pigs/pen).…”
Section: Resultssupporting
confidence: 92%
“…Coated proteases in diets of weaned pigs showed improved apparent total tract digestibility of nitrogen (N) and energy. It also resulted in improved AID of some indispensable amino acids, nutrients (Pan et al, 2016), crude protein and standardized ileal digestibility (Yu et al, 2016). Other studies confirmed that weaned pigs fed protease supplemented diets improved nutrient digestibility and growth performance ( Zuo et al, 2015;Tactacan et al, 2016).…”
Section: Resultsmentioning
confidence: 50%
“…Assessing the nutritional efficiency is a critical factor for animal protein production to understand the nutrient utilization and optimizing the nutrients in the ration, as well as reducing the environmental pollution through undigested nutrients [1]. In the present study, addition of CC protease had shown significantly (P < 0.1) lesser energy and protein intake than other treatment groups [7] (Table 3).…”
Section: Fig 1 Body Weight Gain (G) and Fcr Of Broilers Fed With CC mentioning
confidence: 58%
“…Most of the proteins in soybean are easily digested, except some, like glycinin, protease inhibitors and antigenic proteins which may predispose the intestinal damage and impair the immune function [1]. With the development of enzyme technologies, protease application helps to enhance the protein and amino acid digestibility [2], as well encourages the addition of alternate protein feed materials which helps to reduce the feed cost.…”
mentioning
confidence: 99%